CDNA and gene structures of two phospholipase A2 isoforms, acidic PLA2 PA4 and PLA2 PA3A/PA3B/PA5, in Nemopilema nomurai jellyfish venom. (November 2016) - Heo, Yunwi; Kwon, Young Chul; Shin, Kyoungsoon; Yoon, Won Duk; Han, Chang Hoon; Yum, Seungshic; Kim, Euikyung
Abstract: We have shown that Nemopilema nomurai jellyfish venom (NnV) contains various kinds of proteolytic enzyme activities, including phospholipase (PLA), metalloproteinase (MP) and hyaluronidase activities. In this study, we reported the full-length cDNA and gene sequences of two PLA2 isoforms: acidic PLA2 PA4 and PLA2 PA3A/PA3B/PA5. The full-lengthcDNA of acidic PLA2 PA4 contains 483 nucleotides (nt), which encode 160 amino acids (and the stop codon), including a signal peptide, six cysteine residues that form disulfide bonds, and metal-binding and catalytic active sites. The gene sequence of the acidic PLA2 PA4 is 1667 base pairs (bp) long and encodes three exons and two introns. The 5′ donor (GT) and 3′ acceptor (AG) splice sites are highly conserved. The PLA2 PA3A/PA3B/PA5 gene contains 1366 bp, and the 498 nt of the mature mRNA encode 165 amino acids (and the stop codon). The protein includes a signal peptide, six cysteine residues that form disulfide bonds, and metal-binding and catalytic active sites. The three exons and two introns also have highly conserved donor and acceptor splice sites. InterProScan predicted PLA2 activity domains in both isoforms. These results extend our understanding of the PLA2 venom of the N. nomurai jellyfish and will facilitate further research. Highlights: N. nomurai cnidae extract exhibited phospholipase activity that was inhibited by p -Bromophenacyl bromide ( p -BPB). Hydrolytic activity of PLA2 from NnV by using zymography, the activity showed with a molecular mass of approximately 15 kDa. Full-length cDNA and genomic sequence of PLA2 isoforms of N. nomurai were reported for the first time.